PENILAIAN ASET BEKAS MILIK ASING/CINA DI KABUPATEN BELITUNG TIMUR - , Kuspianto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to appraise the assets of the foreign/Chinese former ownerships in East Belitung Regency. The alternative suggested by the Regional Assistance Team on the former foreign/Chinese ownerships settlement in Jalan Jenderal Sudirman Lipat Kajang (GTB), Desa Baru, Kecamatan Manggar, Belitung Timur was releasing its mastery from the state to the third party by paying compensation to the government by depositing it into the state treasury or certified behalf on the local government. The value of foreign/Chinese asset which was released its mastery from the state to the third party by paying compensation to the government was Rp6.446.322.000,00. The asset value was estimated by using market approach. If the solution taken was certified behalf on the local government, the value of asset in the government balance sheet was Rp Rp354.936.450,00. This value was estimated using Nilai Jual Objek Pajak (NJOP) applied on the area.